Third-Party Reproduction A Comprehensive Guide - Goldfarb, James M. (Springer New York : Imprint: Springer, 2014)
The first IVF conceived birth in 1978 resulted in a significant growth of third party reproductive options which continue to raise ethical, legal, and psychological questions.  Third party reproduction procedures can involve as many as five people:  sperm donor, egg donor, gestational carrier, and intended parents. Third-Party Reproduction: A Comprehensive Guide utilizes experts in the field to address the medical, psychological, ethical and legal aspects of sperm donation, egg donation, embryo donation, and the use of gestational carriers.  In addition, there are chapters on the medical and ethical aspects of posthumous reproduction, religious aspects of third party reproduction, and how to avoid pitfalls of third party reproduction.  Aimed at physicians, trainees, psychologists, nurses, and social workers whose practices may include patients considering third party reproduction, the intent of this book is to provide a comprehensive and practical  overview of the many aspects of third party reproduction to help all those involved to better understand them. Patients considering third party reproduction may also find value in this book.